Relevansi Pemikiran Ki Hadjar Dewantara: Landasan Pendidikan di Era Kurikulum Merdeka Dalam Menghadapi Abad 21 - Sisean Baga; Anang Suprapto; Parmenas Sinaga (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Merdeka Curriculum aims to transform the perspective on education in Indonesia in line with the principles of Ki Hadjar Dewantara's Educational Philosophy (KHD). This philosophy emphasizes the students' needs in the learning process as the primary focus of education. KHD's thoughts form the foundation of the Merdeka Curriculum by optimizing students' potential through the pamong and among system, based on the motto Ing Ngarso Sung Tulodo, Ing Madya Mangun Karso, and Tut Wuri Handayani. These three mottos will be applied in a student-centered approach, with the goal of creating a balance between students' creativity, emotions, and communication. Challenges that can disrupt this balance include moral crises, information distortion, and digital disruptions that weaken students in facing the 21st century. Therefore, education must return to KHD's thinking, where students are guided to discover their potential and overcome the challenges of the 21st century through collaboration. In line with the above explanation, if we reconsider Ki Hajar Dewantara's educational principles in the context of multiliteracy education, this is tangible evidence of Indonesia's efforts to face the future of education, with the goal of achieving Indonesia's vision of creating an excellent generation in 2045.